PENGARUH JUMLAH UANG BEREDAR, BI RATE DAN JUMLAH KASUS COVID TERHADAP RETURN SAHAM SYARIAH - Samiudin, Askal (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
The purpose of this study was to determine the effect of the money supply, the BI Rate and the number of cases of covid 19 on stock returns on the Jakar Islamic Index (JII), the research method used was a quantitative method with a descriptive approach, while the subjects of this study were 15 companies. which is listed on the Jakarta Islamic Index (JII) stock index for the 2020-2021 period, and uses secondary data. data analysis using multiple linear regression using software eviews 10. The results of this study show that the amount of money in circulation does not affect stock returns at JII, the BI Rate affects stock returns at JII, the number of covid 19 cases does not affect stock returns at JII.